1991
DOI: 10.1061/(asce)0733-9364(1991)117:3(486)
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐ and Schedule‐Control Integration: Issues and Needs

Abstract: Cost control and schedule control are two of the most important management functions in the construction industry. Major research efforts are focused on developing procedures for improving the effectiveness of cost and schedule control. As a result, researchers are concerned with the quality, integrity, and timeliness of data that flow through such control systems. A number of data models have been proposed to integrate cost-and schedule-control functions, because such integration is viewed as the, solution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 5 publications
(1 reference statement)
0
45
0
Order By: Relevance
“…Planners and project managers should know the current status (i.e., progress) of their projects in order to avoid misinterpretation of the executed schedule against the planned schedule (Jung & Kang, 2007). According to Rasdorf and Abudayyeh (1991), interdependency between the time and cost of a project calls for a control and feedback system to support decision making, especially when facing the recovery of lost time. Oberlender (2000) stated that an established control process could be explicitly achieved by an operational plan that links the three main components (scope, time, and cost) of the project.…”
Section: Schedule Plan Development and Performance Controlmentioning
confidence: 99%
“…Planners and project managers should know the current status (i.e., progress) of their projects in order to avoid misinterpretation of the executed schedule against the planned schedule (Jung & Kang, 2007). According to Rasdorf and Abudayyeh (1991), interdependency between the time and cost of a project calls for a control and feedback system to support decision making, especially when facing the recovery of lost time. Oberlender (2000) stated that an established control process could be explicitly achieved by an operational plan that links the three main components (scope, time, and cost) of the project.…”
Section: Schedule Plan Development and Performance Controlmentioning
confidence: 99%
“…The key concept of this model is to allot a cost account of specific percentages to a given task. Rasdorf and Abudayyeh (1991) suggested that the work-packaging model is the best model, however it requires collecting excessive amounts of detailed data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For a given work item, alternative measurement methods are available for progress management; an appropriate measurement method is selected for the work item based on the project characteristics; and progress data is collected in the specified data type to determine the progress at the activity level. Although WBS is defined as an integrated structure for schedule and cost control systems [10], WBS and CBS are usually managed separately in reality [11,12], which requires reassignments of budget items in CBS into the corresponding activities in WBS. Therefore, PMF defines a work as an integrated object of cost and schedule.…”
Section: Figure 1 Progress Measurement Frameworkmentioning
confidence: 99%